Citation and the authority of opinions in Roman and Jewish law: The snake oven revisited - Getzler, JS (Vandenhoeck and Ruprecht Unipress, 2014)
An historical study, in honour of Boudewijn Sirks on his retirement, of canons of citation and authority of legal arguments,drawing from ancient Jewish traditions of religious jurisprudence adjacent to late imperial Roman law principles of juridical authority. It begins with the notorious Lex Citandi, the "Law of Citations", also known as the "lex de responsis prudentium", found in the Theodosian Code 1.4.3,later to be replaced by the Justinianic rules of equality of argument. The main part of the paper then looks closely at majoritarian principles in halakhah or Jewish law as preserved in the classical Mishnaic and Talmudic texts. The contrast between the Roman and Jewish systems raises the question whether legal decision-making, involving the sifting and weighing of authorities, is itself a morally important act, or merely a machinery administered by technical experts, of limited spiritual virtue. This is a different problem to the content question — whether the law that binds subjects has any necessary connection to the moral purposes that we pursue in our private and public lives. The ancient jurisprudence suggests a regard for the moral content of the adjudicative process itself.